PENGARUH VARIASI SUHU PENGERINGAN TERHADAP KADAR FLAVONOID TOTAL EKSTRAK UMBI BIT (Beta vulgaris L.) DENGAN METODE SPEKTROFOTOMETRI UV VISIBEL - Susilowati (Universitas Pekalongan, 2025)
Beetroot (Beta vulgaris L.) is one of the plants in Indonesia that is often utilized by the community in a traditional way. Several studies have shown that consuming red beet can improve cardiovascular health and lower daily systolic blood pressure. One of the secondary metabolites that actively plays a role in beetroot is flavonoids. This study aims to determine the highest total flavonoid content in beetroot extract dried using an oven with different drying temperature variations of 60°C, 70°C, and 80°C. The extraction method in this study is maceration using 96% ethanol as the solvent. Qualitative testing was performed with a flavonoid color test using the Taubeck method and Thin Layer Chromatography (TLC) with ammonia vapor. The determination of flavonoid content was done using UV-Visible spectrophotometry. The results showed that beetroot contains flavonoid compounds. The flavonoid content obtained at a temperature of 60°C was 371,11 ± 0 μgQE/g sample, at 70°C it was 357,77 ± 0.0128 μgQE/g sample, and at 80°C it was 241,48 ± 0.0127 mgQE/g sample. It can be concluded that drying temperature affects the total flavonoid content found in beet tubers and the highest flavonoid content obtained is at a temperature of 60°C, which is 371,11 ± 0 μgQE/g sample.